2020
DOI: 10.7554/elife.54309
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans nuclear RNAi factor SET-32 deposits the transgenerational histone modification, H3K23me3

Abstract: Nuclear RNAi provides a highly tractable system to study RNA-mediated chromatin changes and epigenetic inheritance. Recent studies have indicated that the regulation and function of nuclear RNAi-mediated heterochromatin are highly complex. Our knowledge of histone modifications and the corresponding histonemodifying enzymes involved in the system remains limited. In this study, we show that the heterochromatin mark, H3K23me3, is induced by nuclear RNAi at both exogenous and endogenous targets in C. elegans. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…HRDE-1-bound small RNAs can recognize nascent transcripts and recruit chromatin modifiers to establish repressive histone modifications (e.g., H3K9me3) at target genes 22,40 . Neither the histone methyltransferases MET-2 41,42 or SET-32 42,43 nor the chromodomain protein HERI-1 44 was required for silencing (Fig. 3c).…”
Section: Resultsmentioning
confidence: 98%
“…HRDE-1-bound small RNAs can recognize nascent transcripts and recruit chromatin modifiers to establish repressive histone modifications (e.g., H3K9me3) at target genes 22,40 . Neither the histone methyltransferases MET-2 41,42 or SET-32 42,43 nor the chromodomain protein HERI-1 44 was required for silencing (Fig. 3c).…”
Section: Resultsmentioning
confidence: 98%
“…We also observed that deficiency for SET-32, an H3K23 methyltransferase that promotes transgenerational silencing responses to small RNAs, results in progeny with very low levels of Pot1 foci (Fig. 3b , ANOVA p < 10 −8 ) 47 , 50 , 51 .…”
Section: Resultsmentioning
confidence: 61%
“…Although the absence of MET-2 and SET-25 together abolishes all germline H3K9 methylation 47 , we found that these proteins are independently required to promote the stability of Pot1 foci. A third histone methyltransferase that is required for Pot1 focus formation, SET-32, methylates H3K23, which is a heterochromatic mark that has been recently identified in C. elegans 51 , 68 . SET-25 and SET-32 have previously been shown to respond to small RNAs by establishing silent chromosome domains that are then maintained for multiple generations 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Small-RNA-guided chromatin modifications have been widely studied in many organisms. In C. elegan s, NRDE complex transports 22G RNAs from the cytoplasm to the nucleus, induces H3K9, H3K23 and H3K27 trimethylation and mediates transgenerational inheritance of RNAi [25, 34]. In this study, we found that the risiRNA/NRDE complex inhibits RNAP I transcription without altering the status of H3K9 and H3K27 trimethylation of rDNA genes.…”
Section: Discussionmentioning
confidence: 67%
“…We further investigated the molecular mechanism of nucleolar RNAi. Small interference RNAs guide the NRDE complex to targeted pre-mRNAs, induce H3K9, H3K23 and H3K27 trimethylation at the corresponding genomic loci, inhibit RNAP II-mediated transcription elongation, and silence gene expression in the nucleus in C. elegans [19, 20, 24, 25]. To determine whether risiRNAs induce histone modifications, we conducted ChIP assays with anti-H3K9me3 and anti-H3K27me3 antibodies.…”
Section: Resultsmentioning
confidence: 99%